Design of a Project Management Information System (PMIS) Tailored to The Information Requirements of a Web-Based Project - Dhiva Nuraisya; Kartika Hapsari; safri (Politeknik Negeri Jakarta, 2025)
The rapid development of information technology, especially the internet, has revolutionized the way we access and utilize information. In the construction industry, the demand for timely, accurate, and centralized project information has become paramount. By employing web-based dashboards, stakeholders can monitor project progress in real-time, with weekly updates visualized for easy comprehension. A thorough analysis of project information requirements is fundamental to designing a web-based Project Management Information System (PMIS), ensuring that the system effectively meets the specific needs of project monitoring and management. At Rumah Sakit Pusat Otak Nasional Prof. Dr. dr. Mahar Mardiono Jakarta, which is where the research was conducted, the project management information system uses Ms Teams. In addition. With the use of previous PMIS, deficiencies can still be found, such as network connection problems, limited features, and data quality so that in this casefurther research is needed to obtain a more effective system. However, if there are limitations in the delivery of information, obstacles in supervision can occur. This study was conducted with those aim, and also to find out information on the construction process, to analysed the efficiency of the project monitoring relationship with website-based PMIS, and to see the effectiveness of website-based PMIS for the Rumah Sakit Pusat Otak Nasional Prof. Dr. dr. Mahar Mardiono Jakarta. The study was then conducted by collecting data on needs from at least 12 respondents through interviews, questionnaires, to parties who are considered to have a significant influence on the success of this project, such as project managers and informatics engineering experts. The research results show a tendency that website-based PMIS can fulfil and answer information needs in construction projects and increase time efficiency, especially in document distribution. In addition, the completion of features needs to be further considered and developed, specifically related to village display, data visualization, notifications, and accessibility